Chronic care management for patients with COPD: a critical review of available evidence. Issue 5 (2nd December 2011) - Lemmens, Karin M. M.; Lemmens, Lidwien C.; Boom, José H. C.; Drewes, Hanneke W.; Meeuwissen, Jolanda A. C.; Steuten, Lotte M. G.; Vrijhoef, Hubertus J. M.; Baan, Caroline A.
Abstract: Rationale, aims and objectives  Clinical diversity and methodological heterogeneity exists between studies on chronic care management. This study aimed to examine the effectiveness of chronic care management in chronic obstructive pulmonary disease (COPD) while taking heterogeneity into account, enabling the understanding of and the decision making about such programmes. Three investigated sources of heterogeneity were study quality, length of follow‐up, and number of intervention components. Methods  We performed a review of previously published reviews and meta‐analyses on COPD chronic care management. Their primary studies that were analyzed as statistical, clinical and methodological heterogeneity were present. Meta‐regression analyses were performed to explain the variances among the primary studies. Results  Generally, the included reviews showed positive results on quality of life and hospitalizations. Inconclusive effects were found on emergency department visits and no effects on mortality. Pooled effects on hospitalizations, emergency department visits and quality of life of primary studies did not reach significant improvement. No effects were found on mortality. Meta‐regression showed that the number of components of chronic care management programmes explained present heterogeneity for hospitalizations and emergency department visits. Four components showed significant effects on hospitalizations, whereas two components had significant effects on emergency department visits. Methodological study quality and length of follow‐up did not significantly explain heterogeneity. Conclusions  This study demonstrated that COPD chronic care management has the potential to improve outcomes of care; heterogeneity in outcomes was explained. Further research is needed to elucidate the diversity between COPD chronic care management studies in terms of the effects measured and strengthen the support for chronic care management.